Evidence of Renal Iron Accumulation in a Male Mouse Model of Lupus - Theut, Lindsey R.; Dsouza, Del L.; Grove, Ryan C.; Boesen, Erika I. (Frontiers in Medicine, 2020)
Lupus nephritis represents a common and serious complication of the autoimmune disease Systemic Lupus Erythematosus (SLE). Clinical studies suggest that several proteins related to iron metabolism, including transferrin, serve as urinary biomarkers of lupus nephritis. We previously reported that in female NZBWF1 mice, a commonly used mouse model of SLE with a female sex bias, increased urinary transferrin excretion and renal iron accumulation occur around the onset of albuminuria. The current study investigated whether similar findings occur in male mice of a different mouse model of SLE, the MRL/lpr mouse. Two different cohorts were studied: MRL/lpr mice at an early, pre-albuminuric age (8 weeks) and after developing albuminuria (> 100mg/dL, confirmed by ELISA); age-matched MRL/MpJ control strain mice served for comparison. Urinary transferrin excretion was dramatically increased in the older, albuminuric MRL/lpr mice compared to the age-matched MRL/MpJ (P < 0.05), but there was no significant difference between strains at 8 weeks of age. Similarly, there were no significant differences between strains in renal cortical or outer medullary non-heme iron concentrations at 8 weeks. In the older, albuminuric MRL/lpr mice, renal cortical and outer medullary non-heme iron concentrations were significantly increased compared with age-matched MRL/MpJ mice, as was expression of the iron storage protein ferritin (P < 0.01). Together, these data show that increased urinary transferrin excretion and renal tissue iron accumulation also occurs in albuminuric male MRL/lpr mice, suggesting that renal iron accumulation may be a feature of multiple mouse models of SLE.